Optoelectronic properties of ultrathin ALD silicon nitride and its potential as a hole-selective nanolayer for high efficiency solar cells - Khorani, E; McNab, S; Scheul, TE; Rahman, T; Bonilla, RS; Boden, SA; Wilshaw, PR (AIP Publishing, 2020)
Fully exploiting the power conversion efficiency limit of silicon solar cells requires the use of passivating contacts that minimize electrical losses at metal/silicon interfaces. An efficient hole-selective passivating contact remains one of the key challenges for this technology to be deployed industrially and to pave the way for adoption in tandem configurations. Here, we report the first account of silicon nitride (SiNx) nanolayers with electronic properties suitable for effective hole-selective contacts. We use x-ray photoemission methods to investigate ultra-thin SiNx grown via atomic layer deposition, and we find that the band alignment determined at the SiNx/Si interface favors hole transport. A band offset ratio, ΔEC/ΔEV, of 1.62 ± 0.24 is found at the SiNx/Si interface for the as-grown films. This equates to a 500-fold increase in tunneling selectivity for holes over electrons, for a film thickness of 3 nm. However, the thickness of such films increases by 2 Å–5 Å within 48 h in cleanroom conditions, which leads to a reduction in hole-selectivity. X-ray photoelectron spectroscopy depth profiling has shown this film growth to be linked to oxidation, and furthermore, it alters the ΔEC/ΔEV ratio to 1.22 ± 0.18. The SiNx/Si interface band alignment makes SiNx nanolayers a promising architecture to achieve widely sought hole-selective passivating contacts for high efficiency silicon solar cells.